2019
DOI: 10.1111/cen.13907
|View full text |Cite
|
Sign up to set email alerts
|

Cosyntropin testing does not predict response to glucocorticoids in community‐acquired pneumonia in a randomized controlled trial

Abstract: Summary Objective Glucocorticoids have been shown to improve outcome in community‐acquired pneumonia (CAP). However, glucocorticoids have potential side‐effects, and treatment response may vary. It is thus crucial to select patients with high likelihood to respond favourably. In critical illness, cosyntropin testing is recommended to identify patients in need for glucocorticoids. We investigated whether cosyntropin testing predicts treatment response to glucocorticoids in CAP. Design Predefined secondary analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, even a cortisol value above this should not preclude treatment with glucocorticoids if the clinical presentation is consistent with cortisol deficiency. 3 Moreover, even low-dose cosyntropin testing may not predict response to glucocorticoids 4 and thus initial cosyntropin testing may miss secondary cortisol deficiency. 5 We agree with Burgos et al 6 that the patient's clinical presentation should be considered when interpreting cosyntropin tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, even a cortisol value above this should not preclude treatment with glucocorticoids if the clinical presentation is consistent with cortisol deficiency. 3 Moreover, even low-dose cosyntropin testing may not predict response to glucocorticoids 4 and thus initial cosyntropin testing may miss secondary cortisol deficiency. 5 We agree with Burgos et al 6 that the patient's clinical presentation should be considered when interpreting cosyntropin tests.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Steroid benefit does not seem to correlate to the response to a cosyntropin stimulation test in this setting. 25 The benefits of the use of hydrocortisone and fludrocortisone in patients with major trauma are not well established at this time. 5 Relative adrenal insufficiency has also been described in patients with ischemic stroke 26 and has been found to be highly prevalent in patients with liver disease, 27 and burn patients.…”
Section: Therapeutic Approach Of Circimentioning
confidence: 99%
“…In contrast, the CORTICUS trial found no treatment prediction by adrenal function testing with 250 μg synthetic adrenocorticotropin (ACTH) . Similarly, we recently showed that adrenal function testing using the low‐dose 1 μg ACTH test does not predict response to corticosteroid therapy in patients with CAP . Consequently, the current guidelines for the diagnosis and management of CIRCI did not reach consensus in this point and therefore make no recommendation in terms of adrenal function testing in the context of critical illness .…”
Section: Introductionmentioning
confidence: 99%